Arabic Culture As A Defensive Strategy: Tunisian Education As An Example - Khaldi, Boutheina (Ijaz Arabi Journal of Arabic Learning, 2021)
Since independence, the educational system in the Arab world in general, and Tunisia in particular, has continued to alienate itself from the mainstream society. Deeply rooted in a colonial past, education has failed to effect social, economic, and political change. this paper focuses on the status of education, and by extension Arabic language, in Post-independent Tunisia. Using Pierre Bourdieu’s theory of Cultural Reproduction, and Antonio Gramsci’s theory of Cultural Hegemony. The method used is descriptive; to describe the research topic problems qualitatively to draw conclusions objectively according to primary data. The historical method is analyzing past events, interpreting them, and presenting the results to highlight their present and future effects.The finding sets out to argue that educational institutions are sites of power play.